Upper Gastrointestinal Tract Crohn's Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
Crohn's disease may involve any site within the gastrointestinal tract. Usually pathology is present in the ileum and/or colon, but atypical presentations may occur with apparently 'isolated' involvement of the oropharynx, esophagus or gastroduodenum. If changes typical of Crohn's disease are detected in the upper gastrointestinal tract, then a careful assessment is required involving radiographic, endoscopic and histologic studies to determine if pathology is present in more distal intestine. In addition , microbiologic studies may be important to exclude infectious causes, especially of granulomas. If these studies are negative, prolonged follow-up may be required to establish a diagnosis of Crohn's disease. Although upper gastrointestinal involvement is increasingly recognized as a significant cause of morbidity in Crohn's disease, the treatment options are limited , largely anecdotal and need to be the subject of detailed epidemiologic investigation and clinical trials.